Serological Study of Middle East Respiratory Syndrome Corona Virus (MERS-CoV) Strains Circulating Among Camels and Their Handlers in Some Parts of North-Eastern Nigeria - Fatimah, M. M.; Azeez A.; Lawal, D. R.; Taysir H. R. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is increasingly recognized as a significant emerging zoonotic disease of global health concern, affecting camel handlers due to its high mortality rates. However, there is limited data available on this issue in the study areas. This study aimed to assess the relationship between socio-demographic factors, seasonal variation (wet and dry seasons), and the prevalence of MERS-CoV infection among the population in North eastern Nigeria, including Borno, Yobe, and Bauchi States. A total of 780 camel handlers were recruited, with 260 participants from each state. In addition, 120 dromedary camels (40 from each state) were tested for MERS-CoV. Blood samples were screened for MERS-CoV IgM antibodies using an ELISA kit (Axion Diagn, Germany) as per the manufacturer’s instructions. A structured questionnaire was employed to collect socio-demographic data, and the relationship between MERS-CoV sero-prevalence (IgM antibodies) and socio-demographic characteristics /seasonal variation was analysed using SPSS software (version 23.0). The overall sero-prevalence of MERS-CoV infection among camel handlers was 8.1% (63/780), while in camels it was 43.8% (135/240), with higher rates during the dry season (6.8% in handlers and 58.3% in camels), which was statistically significant (P<0.05). MERS-CoV infection was more common in males (7.7%, 60/780) compared to females (0.4%, 3/780), particularly in the 40-49 age group (3.6%, 28/780), and was most prevalent among camel handlers from Borno State (3.5%, 27/780). Factors such as camel rearing, low education levels, and lack of awareness significantly contributed (P<0.05) to the high infection rate. Therefore, public awareness programs focusing on MERS-CoV transmission and preventive measures, especially among camel and animal handlers, are essential to limit the spread of the disease and reduce its associated morbidity and mortality.